A study on the factors that influence motivation among employees in organizations at Taman Pertam Jaya, Padang Temu, Melaka / Nur Syafiqah Athirah Mohd Jaini - Mohd Jaini, Nur Syafiqah Athirah (Faculty of Business and Management, 2014)
“A Study on The Factors That Influence Motivation Among Employees in Organizations at Taman Pertam Jaya, Melaka” Employee is an important asset in the organization. Organization performance is depends on employees in organization. This paper aims to study on the factors that influence motivation among employee in organizations at Taman Pertam Jaya, Melaka. The independents variables that involved in this study are rewards, empowerment and management commitment. For this project paper, this research focused on the employees been worked at Taman Pertam Jaya, Padang Temu, Melaka. 80 questionnaires were distributed to employees. The questionnaires were used to obtain and collected the data from the respondent. Cluster area sampling has been used in this study as a sampling technique. The researcher used SPSS program version 20.0 where the researcher has used reliability analysis, frequency analysis and correlation analysis. In the end of this paper, the researcher has provided several recommendations regarding the factors that influence motivation among employees in organizations at Taman Pertam Jaya, Melaka.